Bahamas. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in the Bahamas during 2014 are identified, with respect to the needs and interests of the country, strengthening issues such as innovation, technology, aquaponics, livestock, greenhouses, markets, poultry farming, data analysis and resilience against climate change. Likewise, work was done to improve slaughterhouses, orphanages, knowledge management and livestock systems. Finally, it supported the inclusion of women and the value chains of sheep, goats, small ruminants, sweet potatoes, cassava and sweet potatoes.